Impact of Organizational Learning on Sustainable Firm Performance: Intervening Effect of Organizational Innovation - Hartarini, Yovita Mumpuni; Marsha Ayunita Irawati,; Risma Musfiana, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research has analyzed the role of learning in an organization while measuring and managing sustainable organizational performance. It also included the intervening role of organizational innovation while examining the relationship between organizational learning and sustainable organizational performance. This research adopted a quantitative approach, using a survey method to collect data from 100 from Pusat Koperasi Karyawan (Puskopkar) Kereta Api Indonesia (KAI) Daerah Operasi and Divisi Regional Kereta Api Indonesia (Daop) 4 Semarang and 5 Purwokerto Central Jawa. This research uses a questionnaire as a research instrument. Structure equation modeling SEM was used through partial least square PLS software to test the collected data. The study’s findings show that organizational learning is vital to organizational performance. The research concludes that organizational learning is very vital for sustainable organizational performance. The current research contributes to the body of knowledge by examining sustainable organizational performance from an entirely different perspective.